Dispersion of natural modes in a many-layer planar system - Goncharenko, A.V.; Snopok, B.A.; Shirshov, Yu.M.; Venger, E.F.; Zavadskii, S.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
We derive the recurrence dispersion equations for natural modes of a many-layer planar system. As an illustration a five-layer planar system is considered, and solutions for guided-wave polaritons of such a system are found. The behavior and peculiarities of these solutions are analyzed.